(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2018)
In the article substantiated the potential opportunities for implementation and successful use of foreign experience for automation of accounting and analytical process at enterprises through the use of modern foreign information systems and technologies, in particular, with the use of differentiated modifications of infosystem «SAP Business One». The example of «SAP» revealed the obstacles that arise in the process of implementation, adjustment and operation of modern foreign automated software products in the current Ukrainian realities. It is proved that the most significant obstacle for the successful implementation of modern foreign automated systems is their low mobility regarding the dynamic changes in the Ukrainian legislative field. The report substantiates that the introduction of modern foreign information systems in the future is prospective only if the patriotic normative-legal regulatory base for accounting and analytical work, as well as the Ukrainian chart of accounts, will be unified in accordance with the requirements of the legislative field and the single European economic space.